Improvement of Methodological Support of Teaching Discipline Information and Communication Technologies in Electronic Educational Environment - Suropov, Bakhodir Maidanovich; Kayumova, Nasiba Ashurovna (International Journal of Psychosocial Rehabilitation, 2020)
This article describes ways to improve the methodological support of teaching the discipline information and communication technologies in the electronic educational environment. The main objectives of the study are also described as the objectives of the study: to determine, analyze the pedagogical and psychological aspects of the problems of teaching the discipline information and communication technologies in the economic areas of higher education; improve the methodological support used in teaching the discipline information and communication technologies in the electronic educational environment; to form the professional competence of students on the basis of pedagogical and information and communication technologies through teaching the discipline information and communication technologies in the electronic educational environment; to develop recommendations for improving the criteria that determine the effectiveness of the organization of the educational process in the electronic educational environment using the improved methodological support of the discipline information and communication technologies. The analysis of factors influencing the improvement of the methodological support of teaching the discipline information and communication technologies in the electronic educational environment is presented. On a theoretical and practical basis of the study, recommendations and conclusions are made.